Fine scale mapping of the structure and composition of the Elkhorn Slough (California, USA) tidal plume. (5th January 2017) - Fischer, Andrew M.; Ryan, John P.; Rienecker, Erich V.
Abstract: Fine scale mapping of the structure and composition of a tidal ebb plume from a highly modified coastal lagoon (Elkhorn Slough, California, USA) was conducted by combining in situ, observational data sets from surface underway mapping, autonomous underwater vehicle (AUV) profiles, drifter tracking and the analysis of plume structure indices. The results reveal a 6-m-deep, jet-like, sediment laden plume extending one km offshore at low tide, which becomes entrained in the prevailing nearshore circulation. The plume that exits the slough is significantly different from the water that enters the slough. The rapidly evolving discharge plume is associated with elevated and highly correlated ( r = 0.93 ) concentrations of dissolved organic matter and nitrate. While dissolved constituents remain in the shallow plume and are transported northward with the prevailing current, sediment may settle quickly through the water column and can be transported southwestward with the littoral currents. This study illustrates the applications of AUVs, when coupled with additional datasets, for generating higher resolution observational snapshots of dynamic and ephemeral tidal plumes. The results provide unique perspective on small-scale dynamics of an estuarine plume and its influence on coastal ecology.